Economic and Non-Economic Variables Affecting Consumer Preferences of Quezon City Households on Sachet Products - Aliyah Jana E. , Aliyah Jana E.; Jalen Arvin H. , Jalen Arvin H.; Oblea, Shaina Nicole R.; Cabauatan, Ronaldo R. (International Journal of Social and Management Studies, 2022)
Sachet managed to progress through time which led to the existence of ‘tingi’ culture throughout the rural and urban areas in the Philippines. Given that sachets are utilized in countries with a massive population, the success of these products has become evident and essential to the daily lives of consumers. This study seeks the relationship between various economic and non-economic variables on consumer preferences of Quezon City households towards purchasing sachet products. Using a non-probability quota sampling, a survey questionnaire is employed to determine how household income, household size, affordability, marketing strategies, reasons for buying sachets, and consumers’ self-regulation are perceived by different households. The findings of this study suggest that sachet consumption is highly affected by the consumer's preferences and purchasing practices due to the phenomenon that has influenced Filipino culture. The researchers of this study aim to fill the gap in research and provide knowledge about mini packets with massive economic impact. Furthermore, the concept of Consumer Theory is also applied which shows that individuals have the right to choose from the options of goods and services that are available, which are bound by several factors, including budget constraints and personal preferences.